Lake County, Tennessee, in the Heart of the New Madrid Seismic Zone - Weathers, Taylor; Van Arsdale, Roy (Frontiers in Earth Science, 2019)
Lake County, Tennessee, lies within the center of the New Madrid seismic zone and thus is particularly vulnerable to seismic hazards. To better evaluate the seismic threat to Lake County, the stratigraphy and structure were mapped beneath the county. A shallow 3-D lithologic model was constructed to illustrate the Quaternary Mississippi River alluvial facies of Lake County in five-foot (1.5 m) thick layers to a depth of 300 feet (91.4 m). This model provides near-surface geologic data for the determination of earthquake liquefaction potential and illustrates the Mississippi River alluvial aquifer for optimum agricultural water exploitation. In addition, faulted structure contour maps were made of the tops of the unconformable Paleozoic, Cretaceous, and Eocene sections. With these structure contour maps a deep 3-D geologic model was built for Lake County, which shows the stratigraphy and structure from the Quaternary to the Paleozoic. Cross sections were also created to illustrate the subsurface geology. The faulted structure contour maps and cross sections reveal Quaternary faulting on the Reelfoot North, Axial, Tiptonville dome backthrust, Lake County Uplift backthrust, Cottonwood Grove, Ridgely, and previously unidentified faults. The maps also illustrate where surface fault rupture may occur and the sense of vertical surface displacement in the event of a future large earthquake.